ADOPSI INOVASI PROGRAM RASA SEJIWA DI PUSKESMAS NANGGALO KOTA PADANG - Raihan Sadwirman; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Kelurahan Siaga Sehat Jiwa (Rasa Sejiwa) Program is a program in the mental health services sector that is adopted by Puskesmas Nanggalo, Padang City, with the aim of to improve health services for people with mental disorders who are in the working area of the Nanggalo Community Health Center through training for mental cadres, monitoring taking medication, and implementing mental health services. The purpose of this study was to determine how the adopting process of the Rasa Sejiwa Program at the Puskesmas Nanggalo, Padang City and to find out what was the supporting factors in the adoption of this innovation. This research uses purposive sampling technique with qualitative research type, using a descriptive approach and the required data both primary and secondary data are obtained by interviewing and documentation techniques for further analysis. The results of this study indicate that the implementation of the innovation adoption of the Sense of Soul Program at Nanggalo Community Health Center, Padang City has gone well. The supporting factors for the adopting process this innovation are cross-sector cooperation, good leadership, and support from the community.Keywords: Innovation Adoption, Mental Health Service